2021
DOI: 10.7759/cureus.20523
|View full text |Cite
|
Sign up to set email alerts
|

The Ability of Ultrasound Sonography (USG) to Detect Intrauterine Growth Restriction (IUGR) in the Third Trimester of Pregnancy With the Gold Standard of IUGR (Parameters by USG Hadlock) as a Diagnostic Criterion

Abstract: To investigate the diagnostic accuracy of the placental thickness measured by ultrasound sonography test (USG) in detecting intrauterine growth restriction (IUGR) babies in the third trimester of pregnancy, keeping IUGR (by parameters using Hadlock) as the gold standard. Methods and materialsThis cross-sectional study was conducted at the radiology department of KRL Hospital from August 5, 2020, to October 25, 2021. Informed written consent was also obtained from each patient, and the hospital's ethical commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
1
0
1
Order By: Relevance
“…We found a sensitivity of 65.5%, specificity of 83.3%, PPV of 98.7%, NPV of 10.8%, and diagnostic accuracy of 66.4%. The results of the current study are comparable with the conclusions of Baghel et al (22) In a similar study conducted by Rafique Z et al, the sensitivity, specificity, positive predictive value, and negative predictive value of placental thickness in the determination of IUGR came out to be 86.30%, 86.70%, 75%, and 92%, respectively, documenting higher sensitivity and negative predictive value about our study (18) . This demonstrates that a measure of placental thickness is a useful indicator in predicting IUGR.…”
Section: Table-3 Sensitivity Specificity Positive Predictive Value An...supporting
confidence: 92%
See 1 more Smart Citation
“…We found a sensitivity of 65.5%, specificity of 83.3%, PPV of 98.7%, NPV of 10.8%, and diagnostic accuracy of 66.4%. The results of the current study are comparable with the conclusions of Baghel et al (22) In a similar study conducted by Rafique Z et al, the sensitivity, specificity, positive predictive value, and negative predictive value of placental thickness in the determination of IUGR came out to be 86.30%, 86.70%, 75%, and 92%, respectively, documenting higher sensitivity and negative predictive value about our study (18) . This demonstrates that a measure of placental thickness is a useful indicator in predicting IUGR.…”
Section: Table-3 Sensitivity Specificity Positive Predictive Value An...supporting
confidence: 92%
“…In one study conducted in Pakistan, the sensitivity of ultrasound to detect low placental thickness was reported as 86.30% and a high specificity of 86.70%. In this study, the diagnostic accuracy of ultrasound was also reported to be 86.40% (18) .…”
Section: Introductionmentioning
confidence: 62%
“…Qəbuledici performans əyriləri (AUC) altında əlavə təhlilin nəticələri, Hadlock və FMF standartları ilə müqayisədə gec populyasion (INTERGROWTH-21st) və fərdi (PRB/NICHD) standartları tərəfindən mənfi perinatal nəticələrin aşkarlanmasının bir qədər yaxşılaşdığını göstərir. Z. Rafique et al [22] hamiləliyin üçüncü üçaylığında uşaqlarda DBİL aşkarlanmasında ultrasəsdən istifadə edərək ciftin qalınlığının ölçülməsinin diaqnostik dəqiqliyini öyrənərək, hamiləliyin 24-36 həftələri arasında ciftin qalınlığının demək olar ki, xətti olaraq artdığını aşkar etdi. Nəticədə, plasentanın qalınlığının və digər amillərin ölçülməsi, xüsusilə hamiləliyin dəqiq müddəti bilinməyən ikinci üçaylığın sonunda və üçüncü üşaylığın əvvəlində, dölün yaşını qiymətləndirmək üçün çox vacibdir.…”
Section: Dölün Bətndaxi̇li̇ İnki̇şaf Ləngi̇məsi̇ni̇n əSas Ultrasəs ə...unclassified